Chemical constituents from the branches of Alangium barbatum and their anti-inflammatory activities. (December 2018) - Xie, Yang-Guo; Zhu, Sheng-lan; Huang, Ying-ying; Guo, Yi-gong; Wu, Guo-jing; Muhammad, Ishaq; Yan, Shi-kai; Jin, Hui-zi; Zhang, Wei-dong
Graphical abstract: Highlights: Two new sesquiterpenes (1 and2 ), one new alkaloid (4 ), one new neolignan glycosides (14 ) were isolated from the branches of Alangium barbatum . Their structures and absolute configuration were established from NMR and CD data. Compounds1, 3, and9 exhibited mild inhibitory effects on NO production at respective 10 μM concentrations with 25.0–32.4% inhibitions. Abstract: Two new sesquiterpenes (1 and2 ), one new alkaloid (4 ), one new neolignan glycoside (14 ), together with 19 known compounds were isolated from the branches of Alangium barbatum . Their structures were established by spectroscopic analysis. The absolute configuration of21 was determined for the first time by single-crystal X-ray diffraction analysis with Cu-Kα irradiation. Some of isolates were evaluated for their inhibitory effects on NO production in LPS-induced RAW264.7 macrophages. Compounds1, 3 and9 at 10 μM concentrations exhibited mild inhibitory effects on NO production in the range of 25.0 to 32.4. Moreover, these compounds at 25 μM concentration were also found to mildly suppress NF-κB activation in TNF-α induced expression of NF-κB-Luc in Hela cells with inhibition percent in the range of 15.0 to 25.0%.